The role of sentinel lymph node mapping in small animal veterinary medicine: A comparison with current approaches in human medicine. (27th November 2017) - Beer, P.; Pozzi, A.; Rohrer Bley, C.; Bacon, N.; Pfammatter, N. S.; Venzin, C.
Abstract : The relevance of regional lymph node (LN) assessment to quantify the metastatic spread of cancer is well recognized in veterinary oncology. Evaluation of LNs is critical for tumour staging. However, sampling the correct LN may not be possible without sentinel lymph node (SLN) mapping. Methods for diagnostic imaging and intraoperative detection of SLNs are well established in human medicine, in particular, the combination of lymphoscintigraphy and intraoperative application of blue dyes. Nevertheless, alternative imaging techniques are available and have gained increasing interest. Successful implementation of these techniques in dogs have been reported in both clinical and experimental studies. This review aims to provide an overview of SLN mapping techniques in human and veterinary medicine.